2022
DOI: 10.1186/s12877-022-03068-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a history of child abuse on cognitive performance: a cross-sectional study in older patients with a depressive, anxiety, or somatic symptom disorder

Abstract: Background Child abuse is a major global burden with an enduring negative impact on mental and physical health. A history of child abuse is consistently associated with worse cognitive performance among adults; data in older age groups are inconclusive. Since affective symptoms and cognitive functioning are interrelated among older persons, a synergistic effect can be assumed in patients with affective symptoms who also have suffered from child abuse. This study examines the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“… 76 Like working memory and set shifting (flexibility), inhibitory control is an essential component of the executive functions, which are higher-order cognitive processes. 77 Thus, our findings extend those of Tjoelker et al, 78 who found that a history of physical maltreatment and emotional neglect is associated with diminished interference control in older individuals with depressive, anxious, and somatic symptoms. A significant correlation was identified by Lund et al 79 in a systematic review between ACEs and executive deficits in children, specifically in relation to maternal depression.…”
Section: Discussionsupporting
confidence: 88%
“… 76 Like working memory and set shifting (flexibility), inhibitory control is an essential component of the executive functions, which are higher-order cognitive processes. 77 Thus, our findings extend those of Tjoelker et al, 78 who found that a history of physical maltreatment and emotional neglect is associated with diminished interference control in older individuals with depressive, anxious, and somatic symptoms. A significant correlation was identified by Lund et al 79 in a systematic review between ACEs and executive deficits in children, specifically in relation to maternal depression.…”
Section: Discussionsupporting
confidence: 88%
“…76 Like working memory and set shifting (flexibility), inhibitory control is an essential component of the executive functions, which are higher-order cognitive processes. 77 Thus, our findings extend those of Tjoelker et al, 78 who found that a history of physical maltreatment and emotional neglect is associated with diminished interference control in older individuals with depressive, anxious, and somatic symptoms. A significant correlation was identified by Lund et al 79 in a systematic review between ACEs and executive deficits in children, specifically in relation to maternal depression.…”
Section: Aces Predict Cognitive Impairments In Mddsupporting
confidence: 85%
“…Intervention strategies targeting the risk factors in early life could reduce the incidence of dementia or substantially delay its onset[ 52 ]. Recent studies have found that low adolescent cognitive ability[ 53 , 54 ] and adverse childhood experiences[ 55 , 56 ] have a significant association with dementia risk in later life. Depression that occurs in childhood and adolescence is often accompanied by varying degrees of cognitive impairment in attention, memory, and executive functioning, or even interrupted educational trajectories[ 4 ].…”
Section: Discussionmentioning
confidence: 99%